A First Look at Spatially Resolved Balmer Decrements at 1.0 < z < 2.4 from JWST NIRISS Slitless Spectroscopy - Matharu, Jasleen; Muzzin, Adam; Sarrouh, Ghassan T. E.; Brammer, Gabriel; Abraham, Roberto; Asada, Yoshihisa; Bradač, Maruša; Desprez, Guillaume; Martis, Nicholas; Mowla, Lamiya; Noirot, Gaël; Sawicki, Marcin; et al. (Astrophysical journal. Letters, 2023)
NRC publication: Yes